KAJIAN ILMU KOMUNIKASI PANDANGAN DAN HARAPAN (studi eksploratif tentang pandangan dan harapan pembelajaran Ilmu Komunikasi pada mahasiswa 5 PTS di DKI Jakarta) - Teguh Priyo Sadono; Rina Nur Chasanah (Bricolage : Jurnal Magister Ilmu Komunikasi, 2016)
Communication Studies in university is a very high study of public interest to learn it, so almost all the universities have faculty and Communication studies program. However, the study of Communication Science is relatively linear and the development of science through verification to test the theory. This fact makes the field of study is not applicable and trapped in the development of knowledge. To avoid the occurrence of cases in the science of Agriculture and Science Administration, which in leave the community then this research is done. This study aims to understand the views and expectations of students semester 7 and above about the study of Communication Science. By using survey method conducted exploration of the object. This research to researched at 320 respondents from 5 PTS in Kopertis III. The results showed that their views on teaching materials Communication Science clearly focused on the development of science. They felt they did not get what they expected with a lecture in Communication Science. Because of that also to equip themselves in the world of work, most want a further study in S2. In conclusion, Communication Science Program is now more to the development of science, less provide applicable provision of communication to students. Keywords: linear, views and expectations